Toward a New Generation of Smart Biomimetic Actuators for Architecture. Issue 19 (24th October 2017) - Poppinga, Simon; Zollfrank, Cordt; Prucker, Oswald; Rühe, Jürgen; Menges, Achim; Cheng, Tiffany; Speck, Thomas
Abstract: Motile plant structures (e.g., leaves, petals, cone scales, and capsules) are functionally highly robust and resilient concept generators for the development of biomimetic actuators for architecture. Here, a concise review of the state‐of‐the‐art of plant movement principles and derived biomimetic devices is provided. Achieving complex and higher‐dimensional shape changes and passive‐hydraulic actuation at a considerable time scale, as well as mechanical robustness of the motile technical structures, is challenging. For example, almost all currently available bioinspired hydraulic actuators show similar limitations due to the poroelastic time scale. Therefore, a major challenge is increasing the system size to the meter range, with actuation times of minutes or below. This means that response speed and flow rate need significant improvement for the systems, and the long‐term performance degradation issue of hygroscopic materials needs to be addressed. A theoretical concept for "escaping" the poroelastic regime is proposed, and the possibilities for enhancing the mechanical properties of passive‐hydraulic bilayer actuators are discussed. Furthermore, the promising aspects for further studies to implement tropistic movement behavior are presented, i.e., movement that depends on the direction of the triggering stimulus, which can finally lead to "smart building skins" that autonomously and self‐sufficiently react to changing environmental stimuli in a direction‐dependent manner. Abstract : State‐of‐the‐art biomimetic hydraulic actuators have two major disadvantages: low mechanical robustness and actuation‐speed impediment by the poroelastic timescale. A concise summary of how plant motions can inspire technical kinetic devices is presented, and solutions for the problems mentioned are discussed.